PENGEMBANGAN MEDIA PEMBELAJARAN UNO CARD SEJARAH PADA MATERI JENIS-JENIS MANUSIA PURBA DI INDONESIA KELAS X.3 SMA YP UNILA BANDAR LAMPUNG - Rahma, Okta; Kurniawan, Putut Wisnu; Hendratama, Ozi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This study aims to develop and assess the feasibility of a UNO card game-based learning media to improve students' understanding of history, specifically the topic of prehistoric humans in Indonesia. The subjects were 10th-grade students at SMA YP UNILA Bandar Lampung, using a research and development (R&D) method through the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results showed that the UNO Card History learning media received a very valid rating from media experts (83%) and from material experts (97%). Trials involving teachers and students also yielded positive responses, with 97% and 91% of teachers, respectively, confirming the media's suitability for use in the learning process. Modifications to the UNO cards with the use of color, images, and interactive elements make the learning experience more engaging and effective. Therefore, UNO Card History can be used as an innovative alternative to improve the quality of history learning at SMA YP UNILA Bandar Lampung.